PENGARUH PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Putri Angelina; Ika agustina; Ujang Kusnaedi (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study examines the effect of profitability on tax avoidance, with firm size as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This research employs a quantitative approach based on agency theory, which explains conflicts of interest between management and shareholders in corporate decision-making, including tax strategies. The data used are secondary data obtained from the annual financial statements of the companies. A total of 22 companies were selected using purposive sampling. Data analysis was carried out using Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results indicate that profitability has a significant effect on tax avoidance, meaning that higher profitability increases the tendency of companies to reduce their tax burden. However, firm size does not moderate the relationship between profitability and tax avoidance. This finding suggests that internal financial performance, particularly profitability, plays a more dominant role in influencing tax avoidance practices than firm size in Indonesian mining companies.